From the Booth to the Cloud – Didactic Observations on Simultaneous Interpreting - Filimon Eliza Claudia (Romanian Journal of English Studies)
The present study includes observations on on-site (OSI) ans remote (RSI) simultaneous interpreting approached from two perspectives, that of an interpreter and that of a professor. Having taught this audiovisual translation mode for two decades while periodically doing simultaneous interpreting for equally long, I have noticed the added challenges following the 2020 COVID pandemic which have led to an imbalanced adaptation: as a simultneous interpeter, I had to learn rapidly from each obstacle faced when thrown into Remote simultaneous interpreting (RSI), while my teaching approach was informed by my experience. Given that technological advancements take the job market by storm, training in remote simultaneous interpreting need to keep up by focusing on raising awareness of the differences which increase the difficulty of remote oral transfer.